ANALISIS DAMPAK UKURAN PERUSAHAAN TERHADAP BIAYA LINGKUNGAN DAN EMISI KARBON - Si Made Ngurah Purnaman; Andi Muhammad Fuad Ramadhan; Taufan Sufatriansa Awal (Jurnal Akuntansi dan Bisnis, 2025)
This study explores how company size affects environmental costs and carbon emission transparency in Indonesia's metal and mining sector. Despite its economic importance, the industry contributes heavily to environmental harm. Analyzing secondary data from 20 listed companies, most are classified as large firms. Environmental cost reporting varies greatly, from IDR 35 million to IDR 708 billion. Five companies lack valid carbon data or fall short of OJK standards, while PT Trimegah Bangun Persada records the highest emissions. Larger companies tend to report more extensively, though not always comprehensively. The study highlights the need for stricter regulations to ensure environmental reporting transparency.